Voltage-resistant electrolyte and lithium ion battery using same

By introducing functional additive A into the lithium-ion battery electrolyte, an efficient SEI film and CEI film are formed, the problem of degradation of the electrolyte under high voltage is solved, and the good cycle stability and capacity retention of the lithium-ion battery under high voltage conditions is achieved.

CN119786731AActive Publication Date: 2025-04-08EVE ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411985706.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolytes are prone to oxidation and decomposition under high voltage, resulting in reduced performance. Most of the existing high-voltage electrolyte additives are single positive electrode film forming function, with fewer types, making it difficult to meet the needs of multifunctional high-voltage applications.

Method used

A pressure-resistant electrolyte is used, which comprises an organic solvent component, a lithium salt component and an additive component, and the additive component includes a functional additive A. Functional additive A can form dense SEI films and CEI films on the positive and negative electrode surfaces through the carbon-carbon double bonds and oxygen-silice bond functional groups in its structure, reducing interfacial side reactions, and improving the high voltage cycle process by eliminating water and hydrofluoric acid.

Benefits of technology

It effectively reduces the positive and negative interface side reactions of lithium-ion batteries under high voltage, improves the high-voltage application performance of lithium-ion batteries, and extends the battery's cycle stability and capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786731A_ABST
    Figure CN119786731A_ABST
Patent Text Reader

Abstract

The invention provides a voltage-resistant electrolyte which comprises an organic solvent component, a lithium salt component and an additive component, and the additive component comprises a functional additive A; the structural general formula of the functional additive A is # imgabs0 #, R11, R12 and R13 are independently selected from hydrogen or C1-C4 alkyl or C1-C4 substituted alkyl, R2 is cyanomethyl or cyanoethyl, and at least one of R3 and R4 comprises a carbon-carbon double bond; the molar mass of the functional additive A is 180-280, and the mass ratio of the functional additive A in the voltage-withstanding electrolyte is 0.3 wt.%-1 wt.%. The functional additive A can form a CEI film and an SEI film on the surfaces of the positive electrode and the negative electrode of the lithium ion battery respectively, electrode interface side reactions of the lithium ion battery in the cycle working process are effectively reduced, in addition, the functional additive A shows obvious superiority under the high-voltage application condition, and the application range is wide. Therefore, the voltage-resistant electrolyte can effectively improve the conditions of capacity fading and voltage drop of a battery product in a high-voltage circulation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to a pressure-resistant electrolyte and a lithium ion battery using the same. Background Art

[0002] As pure electric vehicles, hybrid vehicles and portable energy storage devices continue to increase the energy density of lithium-ion batteries, people are looking forward to developing lithium-ion batteries with higher energy density and power density to achieve long-term endurance and energy storage of electric devices. High operating voltage is one of the methods to increase the energy density of lithium-ion batteries. Under high operating voltage, the electrolyte needs to have good oxidation resistance and a stable electrochemical window to ensure that lithium-ion batteries can maintain stable circulation under high voltage.

[0003] However, commercial lithium-ion battery electrolytes are generally composed of carbonate organic solvents and lithium hexafluorophosphate (LiPF6). Carbonate solvents are mainly composed of chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and cyclic carbonates such as propylene carbonate (PC) and ethylene carbonate (EC). However, the above organic solvents have low oxidation potentials and are prone to oxidative decomposition under high voltages and are difficult to exist stably, resulting in reduced performance of lithium-ion batteries containing these solvents in the electrolyte.

[0004] The voltage resistance of commercial electrolytes can usually be improved by:

[0005] (1) Increasing the lithium salt concentration in the electrolyte containing carbonate solvents increases the number of complexes between lithium ions and solvent molecules, which enhances the antioxidant properties of the complexed solvent molecules and the stability of the electrolyte. In addition, compared with traditional electrolytes, high-concentration electrolytes have enhanced flame retardancy and improved battery safety.

[0006] (2) Use new high-voltage electrolyte solvents to replace carbonate solvents. The new solvents include sulfones, nitriles, ionic liquids and fluorinated electrolytes. These new system electrolytes can meet the high voltage requirements to a certain extent.

[0007] (3) By adding high-voltage electrolyte additives to traditional carbonate electrolytes, the additives can preferentially decompose on the positive electrode surface to form a CEI film during battery cycling, which can protect the integrity of the high-voltage electrode material to a certain extent and reduce the side reactions caused by the contact between the high-voltage positive electrode and the electrolyte.

[0008] Although the above methods can improve the high voltage resistance of the electrolyte to a certain extent, they all have certain limitations. High lithium salt concentration will bring about the problem of high cost and low safety of the electrolyte. Sulfone solvents and ionic liquids have relatively high melting points, which makes the performance at low temperatures decrease. The poor compatibility of nitrile with graphite negative electrode and other problems also limit the practical application of new solvent system electrolytes. Fluorinated solvents are prone to produce corrosive HF byproducts that destroy the positive electrode interface, leading to the dissolution of transition metal ions and causing the rapid decline of lithium metal battery performance. In comparison, high-voltage multifunctional additives can simply and effectively improve the high voltage resistance of the electrolyte, but the high-voltage electrolyte additives that can be used on the market currently all have a single positive electrode film-forming function, and there are relatively few types. Therefore, the development of new practical multifunctional high-voltage electrolyte additives is still an urgent problem to be solved. Summary of the invention

[0009] The present invention provides an electrolyte and a lithium ion battery using the same. The electrolyte has good stability and can form a CEI film and a SEI film with excellent performance at the positive electrode and the negative electrode of the lithium ion battery, respectively, thereby effectively reducing the positive and negative electrode interface side reactions of the lithium ion battery under high-voltage working conditions and improving the high-voltage application performance of the lithium ion battery.

[0010] According to a first aspect of the present invention, a voltage-resistant electrolyte is provided, the electrolyte comprising an organic solvent component, a lithium salt component and an additive component, the additive component comprising a functional additive A; the general structural formula of the functional additive A is: Wherein, R11, R12, and R13 are independently selected from hydrogen or C1-C4 alkyl or C1-C4 substituted alkyl, R2 is cyanomethyl or cyanoethyl, and at least one of R3 and R4 includes a carbon-carbon double bond; the molar mass of the functional additive A is 180-280, and in the voltage-resistant electrolyte, the mass proportion of the functional additive A is 0.3wt.%-1wt.%. In the structure of the functional additive A, the olefin structure corresponding to the carbon-carbon double bond is easily reduced to form a dense and uniform SEI film, inhibiting the reduction of transition metal ions on the surface of the negative electrode, thereby reducing the interface side reaction, and the oxygen-silicon bond functional group can react with the water generated by the electrolyte to form O-Si-O substances on the surface of the positive electrode, which can promote the formation of a stable CEI film, thereby effectively reducing the side reactions between the positive electrode and the electrolyte. At the same time, the oxygen-silicon bond can also eliminate water and hydrofluoric acid in the electrolyte, reduce the harm caused by them, and improve the high-voltage cycle process. In addition to having both positive and negative electrode film-forming properties, functional additive A can show obvious superiority under high-voltage application conditions compared to the currently commonly used silicon oxide electrolyte additives and olefin electrolyte additives, so that the voltage-resistant electrolyte of this scheme can effectively improve the capacity attenuation and voltage drop of battery products during high-voltage cycling.

[0011] Preferably, the general structural formula of the functional additive A is Wherein, R5 is hydrogen or C1-10 alkyl or C1-10 alkoxy or C1-10 halogenated alkyl or C1-10 halogenated alkoxy, and R6 is alkyl or substituted alkyl. By further optimizing the chemical structure of the functional additive A, the capacity retention rate of the battery product based on the pressure-resistant electrolyte provided by this solution under high temperature and high pressure application conditions is improved.

[0012] Preferably, the general structural formula of the functional additive A is R7, R8, R9, and R10 are independently selected from hydrogen or C1-10 alkyl or C1-10 alkoxy or C1-10 halogenated alkyl or C1-10 halogenated alkoxy.

[0013] Preferably, the additive component also includes a sulfur-containing additive and vinylene carbonate, wherein the sulfur-containing additive includes at least one of vinyl sulfate (DTD), 1,3-propane sultone (PS), and 1,3-propylene sultone (PST), and the carbonate additive includes vinylene carbonate (VC); the lithium salt component includes lithium hexafluorophosphate (LiPF6) and a lithium salt additive, and the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), and lithium difluorobis(oxalatophosphate) (LiODFP).

[0014] Preferably, the sulfur-containing additive includes 1,3-propane sultone. Based on the functional additive A selected in this solution, the introduction of PS into the electrolyte formula can play a significantly better auxiliary role in the positive and negative electrode film formation for the functional additive A than other sulfur-containing additives.

[0015] Preferably, the lithium salt additive includes lithium difluorophosphate. Based on the application of functional additive A, lithium difluorophosphate is further selected as the lithium salt additive. Functional additive A and lithium difluorophosphate are used together as film-forming substances on the surface of positive and negative electrodes. The two synergistically enhance the effect, making the positive and negative electrode film-forming effect better.

[0016] Preferably, calculated by mass ratio, functional additive A: sulfur-containing additive: lithium salt additive = 0.3-1: 0.5-3: 0.5-1. By adjusting the ratio of functional additive A to sulfur-containing additive and lithium salt additive, the density of SEI film can be further improved while keeping the film formation impedance at a low level.

[0017] Preferably, the organic solvent component includes cyclic carbonates, chain carbonates and chain carboxylates.

[0018] Preferably, the cyclic carbonate includes fluoroethylene carbonate and ethylene carbonate, the chain carbonate includes diethyl carbonate, the chain carboxylic acid ester includes diethyl carbonate, and the chain carboxylic acid ester includes ethyl difluoroacetate; in the voltage-resistant electrolyte, the total mass of fluoroethylene carbonate and ethylene carbonate: the mass of diethyl carbonate: the mass of ethyl difluoroacetate = 1-15: 2-70: 5-20. The CEI film that can be formed on the surface of the positive electrode of the battery based on the functional additive A can provide reliable protection for the positive electrode. On this basis, by optimizing the solvent component, not only can the cycle characteristics of the voltage-resistant electrolyte be further improved, but also a good dissolution medium can be provided for various active ingredients in the electrolyte, thereby improving the film formation quality of the positive electrode CEI film and the negative electrode SEI film.

[0019] According to a second aspect of the present invention, a lithium ion battery is provided, the lithium ion battery comprising the pressure-resistant electrolyte as described above. The lithium ion battery provided by this solution has good high-voltage application performance and can maintain good cycle stability under high-voltage application conditions. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0021] Example 1

[0022] According to the mass percentage of the components, the electrolyte formula used in this embodiment is as follows: functional additive A 0.5%, VC 0.5%, LiPO2F2 0.5%, PS2%, lithium hexafluorophosphate (LiPF6) 15%, and the balance is an organic solvent component. Wherein, the organic solvent component in the above electrolyte formula is composed of fluoroethylene carbonate, ethylene carbonate, diethyl carbonate, and ethyl difluoroacetate. Wherein, based on the total mass of the organic solvent as 100%, the mass proportion of fluoroethylene carbonate is 5%, the mass proportion of ethylene carbonate is 20%, the mass proportion of diethyl carbonate is 65%, and the mass proportion of ethyl difluoroacetate is 10%. Different experimental groups are set with the functional additive A in the above formula as a variable, which are marked as: experimental group 1-1, experimental group 1-2, experimental group 1-3, experimental group 1-4, experimental group 1-5, experimental group 1-6, and experimental group 1-7. The functional additive A used in each of the above experimental groups is shown in Table 1.

[0023] Table 1. Numbers of the experimental groups in this example and their corresponding functional additives A

[0024]

[0025]

[0026] Each experimental group prepared materials according to the electrolyte formula composition adopted by it. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, PS, LiPO2F2, functional additive A, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby making the electrolyte.

[0027] Comparative Example 1

[0028] This comparative example uses the electrolyte formula used in Example 1 as a reference, and uses the functional additive A in the electrolyte formula as a variable to set control group 1-1, control group 1-2, control group 1-3, and control group 1-4. The difference between the electrolyte formula used in the above control groups and the electrolyte formula used in Example 1 is:

[0029] Control group 1-1, omitting the functional additive A in the electrolyte formula of Example 1, and replacing the functional additive A in the electrolyte formula of Example 1 with the organic solvent component of equal mass to form the electrolyte formula used in control group 1-1;

[0030] Control group 1-2 and control group 1-3, as shown in Table 2, respectively use different types of silicon oxide compounds to replace the functional additive A in the electrolyte formula of Example 1 in equal amounts to form the electrolyte formulas used in control group 1-2 and control group 1-3 respectively;

[0031] Control groups 1-4 respectively substituted the functional additive A in the electrolyte formulation of Example 1 with VC in equal amounts to form the electrolyte formulations used in control groups 1-4.

[0032] Table 2. Numbers of the experimental groups in this example and the corresponding silicon oxide compounds used

[0033]

[0034] Except for the above differences, other materials in the electrolyte formula used in the control group 1-1, the control group 1-2, the control group 1-3, and the control group 1-4 are consistent with the materials and proportions used in the electrolyte formula of Example 1.

[0035] The control group 1-1 and the control group 1-4 were prepared according to the electrolyte formula composition used. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, PS, LiPO2F2, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.

[0036] Control group 1-2 and control group 1-3 prepared materials according to their respective electrolyte formula compositions. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, PS, LiPO2F2, silicon oxides, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.

[0037] Preparation Example 1

[0038] The electrolyte used to prepare the lithium ion battery in this preparation example is the electrolyte prepared in Example 1 and Comparative Example 1. The method for preparing the lithium ion battery in this preparation example is as follows:

[0039] Graphite was used as the negative electrode active material. Graphite, conductive agent acetylene black, binder CMC, and SBR were prepared into a negative electrode slurry in a mass percentage of 94:1:2:3. The negative electrode slurry was coated on a copper foil current collector and vacuum dried to obtain a negative electrode sheet. 0.25Li2MnO3·0.75LiMn 0.375 Ni 0.375 Co 0.25 O2 is used as the positive electrode active material, and the positive electrode active material, conductive agent acetylene black, and binder PVDF are prepared into a positive electrode slurry in a mass ratio of 94:3:3. The positive electrode slurry is coated on an aluminum foil current collector and vacuum dried to obtain a positive electrode sheet. The electrolyte prepared in Example 1 and Comparative Example 1 is respectively used to assemble the above-mentioned positive electrode sheet, the negative electrode sheet, and the Celgard2400 separator into a soft-pack battery.

[0040] Test Example 1

[0041] 1. Test subjects

[0042] The soft-pack battery prepared in Preparation Example 1 was used as a test object.

[0043] 2. Test items

[0044] The Xinwei charge and discharge test cabinet is used to conduct cycle performance test on the test object.

[0045] (1) Normal temperature cycle performance test

[0046] At 25°C, the test object is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The test object is subjected to 1000 charge and discharge cycles at 25°C under the above conditions.

[0047] The capacity retention rate (%) of the test object after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium ion battery.

[0048] The average voltage (V) of the test object after N cycles = the discharge energy of the Nth cycle / the discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.

[0049] (2) High temperature cycle performance test

[0050] At 45°C, the test object is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The test object is subjected to 800 charge and discharge cycles at 45°C under the above conditions.

[0051] The capacity retention rate (%) of the test object after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium ion battery.

[0052] The average voltage (V) of the test object after N cycles = the discharge energy of the Nth cycle / the discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.

[0053] 3. Test results

[0054] The test results are shown in Table 3. Under the same test conditions, among the test objects in this test example, the lithium-ion batteries using the electrolytes prepared by Experimental Group 1-1, Experimental Group 1-2, Experimental Group 1-3, Experimental Group 1-4, Experimental Group 1-5, and Experimental Group 1-6 respectively had higher cycle capacity retention rates.

[0055] The electrolytes prepared in the experimental groups 1-1, 1-2, 1-3, 1-4, 1-5 and 1-6 respectively contain the general structural formula conforming to A functional additive (functional additive A), in the above general structural formula, R11, R12, R13 are independently selected from hydrogen or C1-C4 alkyl or C1-C4 substituted alkyl, R2 is cyanomethyl or cyanoethyl, and at least one of R3 and R4 includes a carbon-carbon double bond. When the electrolytes prepared by Experimental Group 1-1, Experimental Group 1-2, Experimental Group 1-3, Experimental Group 1-4, Experimental Group 1-5, and Experimental Group 1-6 are used in the working process of lithium-ion batteries, the olefin structure corresponding to the carbon-carbon double bond in the functional additive A is easily reduced to form a dense and uniform SEI film, which inhibits the reduction of transition metal ions on the negative electrode surface, thereby reducing interfacial side reactions, and the oxygen-silicon bond functional group in the functional additive A can react with the moisture generated by the electrolyte to form O-Si-O substances on the positive electrode surface, which can promote the formation of a stable CEI film, thereby effectively reducing the side reactions between the positive electrode and the electrolyte. At the same time, the above-mentioned oxygen-silicon bonds can also eliminate water and hydrofluoric acid in the electrolyte, reduce the harm they bring, and improve the high-voltage cycle process.

[0056] In the process of preparing the electrolyte of the control group 1-1, the raw materials used do not contain silicon oxide compounds. The test results show that under the same test conditions, the lithium-ion battery prepared by using the electrolyte of the control group 1-1 has the lowest cycle capacity retention rate. In the process of preparing the electrolyte of the control group 1-4, silicon oxide compounds are also not used as raw materials. However, the difference from the control group 1-1 is that the raw materials used to prepare the electrolyte of the control group 1-4 also include VC, which is an olefin SEI film-forming agent commonly used in the prior art. However, from the test results, under the same test conditions, compared with the lithium-ion battery using the electrolyte of the control group 1-1, the corresponding measured cycle capacity retention rate of the lithium-ion battery using the electrolyte of the control group 1-4 is not significantly improved. This shows that under high-voltage working conditions, simply adding an SEI film-forming agent to the electrolyte is not enough to effectively improve the cycle performance of the lithium-ion battery.

[0057] In the process of preparing electrolyte, both control groups 1-2 and 1-3 used silicon oxide compounds as raw materials. However, from the material structure shown in Table 2, it can be clearly seen that the molecular structures of silicon oxide compounds VIII and silicon oxide compounds IX used in control groups 1-2 and 1-3 respectively do not conform to the general structural formula of the functional additive A. Among them, although the molecular structure of silicon oxide compound VIII used in control group 1-2 also contains oxygen-silicon bonds, carbon-carbon double bonds and cyano groups, from the perspective of molecular structure, the arrangement and connection of the above functional groups in the molecular structure of silicon oxide compound VIII are different from the general structural formula of functional additive A. The molecular structure of silicon oxide compound IX used in control group 1-3 does not contain carbon-carbon double bonds, and its molecular structure is obviously different from the general structural formula of functional additive A. From the test results, under the same test conditions, compared with the lithium-ion batteries using the electrolytes of the experimental groups 1-1, 1-2, 1-3, 1-4, 1-5, and 1-6, the cycle capacity retention rates of the lithium-ion batteries using the electrolytes of the control groups 1-2 and 1-3 were significantly lower. The test results show that compared with general silicon oxides, the functional additive A used to prepare the electrolytes of the experimental groups 1-1, 1-2, 1-3, 1-4, 1-5, and 1-6 makes these electrolytes show better cycle characteristics under high-voltage application conditions.

[0058] As described above, based on the test results of this test example, the lithium-ion batteries using the electrolytes prepared by Experimental Group 1-1, Experimental Group 1-2, Experimental Group 1-3, Experimental Group 1-4, Experimental Group 1-5, and Experimental Group 1-6, respectively, can maintain good cycle stability under different temperature conditions. In the above-mentioned experimental groups, the difference is that the silicon oxide compounds used to prepare the electrolytes are different. Based on the above-mentioned difference, the electrolytes prepared by the above-mentioned experimental groups and the lithium-ion batteries using the same also have certain differences in cycle stability and operating voltage. In the lithium-ion batteries using the electrolytes prepared by the above-mentioned experimental groups, under the same test conditions, the lithium-ion batteries using the electrolytes prepared by Experimental Group 1-1, Experimental Group 1-2, and Experimental Group 1-3, respectively, can achieve a higher cycle capacity retention rate and a higher average voltage. The molecular structure of the silicon oxide compound used to prepare the electrolyte in Experimental Group 1-1, Experimental Group 1-2, and Experimental Group 1-3 conforms to the following general formula However, the molecular structure of the silicon oxide compounds used in experimental groups 1-4, 1-5, 1-6, and 1-7 does not conform to the above general formula. Furthermore, compared with the electrolyte of the control group 1-1, among the electrolytes prepared in all the experimental groups, the electrolyte prepared in the experimental group 1-1 can improve the capacity retention rate of the lithium-ion battery to the greatest extent. And under the same test conditions, the lithium-ion battery using the electrolyte prepared in the experimental group 1-1 can achieve the highest average voltage. In summary, when the silicon oxide compound belonging to the functional additive A is used as a raw material to prepare the electrolyte, by further selecting a silicon oxide compound with a specific molecular structure to participate in the preparation of the electrolyte, the cycle performance and average voltage of the lithium-ion battery using this type of electrolyte under high-voltage working conditions can be further improved.

[0059] Table 3. Test result statistics of test case 1

[0060]

[0061] Example 2

[0062] This embodiment uses the electrolyte formula used in the experimental group 1-1 of the embodiment 1 as a reference, and uses the sulfur-containing additive included in the formula as a variable to set the experimental group 2-1, experimental group 2-2, and experimental group 2-3. The electrolyte formulas used in the experimental groups 2-1 and 2-2 are different from the electrolyte formula used in the experimental group 1-1 of the embodiment 1 in that different types of sulfur-containing additives are used to replace the PS in the electrolyte formula of the experimental group 1-1 of the embodiment 1 in equal quality, wherein the sulfur-containing additive used in the experimental group 2-1 is PST, and the sulfur-containing additive used in the experimental group 2-2 is DTD. The electrolyte formula used in Experimental Group 2-3 is different from the electrolyte formula used in Experimental Group 1-1 of Example 1 in that the electrolyte formula of Experimental Group 2-3 does not contain sulfur-containing additives. The electrolyte formula used in Experimental Group 1-1 of Example 1 is used as a reference, and the PS contained in the electrolyte formula is discarded. The original content of PS in the electrolyte formula is supplemented by the organic solvent component used in the electrolyte formula in an equal amount, and the electrolyte formula obtained in this way is used as the electrolyte formula used in Experimental Group 2-3.

[0063] Experimental Group 2-1, Experimental Group 2-2, and Experimental Group 2-3 were prepared according to their respective electrolyte formula compositions. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, sulfur-containing additives, LiPO2F2, silicon oxide I, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.

[0064] Comparative Example 2

[0065] This embodiment uses the electrolyte formula used in the control group 1-1 of comparative example 1 as a reference, and uses the sulfur-containing additive included in the formula as a variable to set control group 2-1, control group 2-2, and control group 2-3. The electrolyte formulas used in the control group 2-1 and control group 2-2 are different from the electrolyte formula used in the control group 1-1 of comparative example 1 in that different types of sulfur-containing additives are used to replace the PS in the electrolyte formula of the control group 1-1 of comparative example 1 in equal mass, wherein the sulfur-containing additive used in the control group 2-1 is PST, and the sulfur-containing additive used in the control group 2-2 is DTD. The electrolyte formula used in the control group 2-3 is different from the electrolyte formula used in the control group 1-1 of the comparative example 1 in that the electrolyte formula of the control group 2-3 does not contain sulfur-containing additives. The electrolyte formula used in the control group 1-1 of the comparative example 1 is used as a reference, and the PS contained in the electrolyte formula is discarded. The original content of PS in the electrolyte formula is supplemented by the organic solvent component used in the electrolyte formula in an equal amount, and the electrolyte formula obtained in this way is used as the electrolyte formula used in the control group 2-3.

[0066] Control group 2-1, control group 2-2, and control group 2-3 were prepared according to the electrolyte formula compositions used respectively. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, sulfur-containing additives, LiPO2F2, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby preparing the electrolyte.

[0067] Preparation Example 2

[0068] The electrolyte used to prepare the lithium ion battery in this preparation example is the electrolyte prepared in Example 2 and Comparative Example 2. The electrolytes prepared in Example 2 and Comparative Example 2 were used to prepare lithium ion batteries in the same manner as in Preparation Example 1. Except for the difference in the composition of the electrolyte used, the other materials and related process steps used in preparing the lithium ion battery in this preparation example were consistent with those in Preparation Example 1.

[0069] Test Example 2

[0070] 1. Test subjects

[0071] The soft-pack battery prepared in Preparation Example 2 was used as a test object.

[0072] 2. Test items

[0073] The Xinwei charge and discharge test cabinet is used to conduct cycle performance test on the test object.

[0074] (1) Normal temperature cycle performance test

[0075] The relevant operations are consistent with those in Test Example 1.

[0076] (2) High temperature cycle performance test

[0077] The relevant operations are consistent with those in Test Example 1.

[0078] 3. Test results

[0079] The test results are shown in Table 4. For ease of comparison, Table 4 shows the high-temperature cycle performance test results of the lithium-ion batteries based on the electrolytes provided by the experimental group 1-1 of Example 1 and the control group 1-1 of Comparative Example 1 in Test Example 1. Therefore, the electrolyte formulas of the experimental group 2-3 and the electrolyte formulas of the control group 2-3 do not contain sulfur-containing additives. Therefore, in Table 4, the contents of sulfur-containing additives are indicated by "-" in the corresponding positions of the experimental group 2-3 and the control group 2-3.

[0080] Among the electrolytes of experimental group 1-1, experimental group 2-1, experimental group 2-2 and experimental group 2-3, the electrolyte of experimental group 2-3 does not contain sulfur-containing additives, and the electrolyte of experimental group 1-1, the electrolyte of experimental group 2-1 and the electrolyte of experimental group 2-2 contain different types of sulfur-containing additives, among which the sulfur-containing additive used to prepare the electrolyte of experimental group 1-1 is PS, the sulfur-containing additive used to prepare the electrolyte of experimental group 2-1 is PST, and the sulfur-containing additive used to prepare the electrolyte of experimental group 2-2 is DTD. Based on the above differences, under the same test conditions, compared with the lithium-ion battery using the electrolyte of experimental group 2-3, the capacity retention rate of the lithium-ion battery using the electrolyte of experimental group 2-1 and the electrolyte of experimental group 2-2 is lower, but the lithium-ion battery using the electrolyte of experimental group 1-1 can achieve a higher capacity retention rate and a higher average voltage value. This shows that in the electrolyte system based on functional additive A, not all sulfur-containing additives can improve the cycle performance of the electrolyte. Among them, the combination of PS and additive A can improve the cycle performance of the electrolyte and enhance the cycle stability and average voltage of the lithium-ion battery using it.

[0081] In the electrolytes of control group 1-1, control group 2-1, control group 2-2 and control group 2-3, the electrolyte of control group 2-3 does not contain sulfur-containing additives, and the electrolyte of control group 1-1, control group 2-1 and control group 2-2 contain different types of sulfur-containing additives, among which the sulfur-containing additive used in the preparation of electrolyte in control group 1-1 is PS, the sulfur-containing additive used in the preparation of electrolyte in control group 2-1 is PST, and the sulfur-containing additive used in the preparation of electrolyte in control group 2-2 is DTD. Based on the above differences, the cycle performance and average voltage of lithium-ion batteries using the above electrolytes under high-voltage working conditions are different. However, under the same test conditions, among the lithium-ion batteries using the electrolytes prepared by the above control groups, the lithium-ion battery using the electrolyte without sulfur-containing additives (control group 2-3) has the highest measured capacity retention rate, while the lithium-ion battery using the electrolyte containing PS (control group 1-1) has the lowest measured capacity retention rate.

[0082] The above comparison shows that the further addition of sulfur-containing additives has different effects on the performance of the electrolyte and the lithium-ion battery using it, depending on whether the electrolyte contains functional additive A. For the electrolyte containing functional additive A, with PS as the sulfur-containing additive, PS can play a significantly better role in assisting the positive and negative electrode film formation of functional additive A than other sulfur-containing additives, thereby making the electrolyte and the lithium-ion battery using it have better cycle characteristics.

[0083] Table 4. Test result statistics of test case 2

[0084]

[0085] Example 3

[0086] This embodiment uses the electrolyte formula used in the experimental group 1-1 of the embodiment 1 as a reference, and uses the lithium salt additive included in the formula as a variable to set the experimental group 3-1, experimental group 3-2, experimental group 3-3, and experimental group 3-4. Compared with the electrolyte formula used in the experimental group 1-1 of the embodiment 1, the electrolyte formula used in the experimental group 3-1, experimental group 3-2, and experimental group 3-3 is different in that different types of lithium salt additives are used to replace the LiPO2F2 in the electrolyte formula of the experimental group 1-1 of the embodiment 1 in equal quality, wherein the lithium salt additive used in the experimental group 3-1 is LiFSI, the lithium salt additive used in the experimental group 3-2 is LiBOB, and the lithium salt additive used in the experimental group 3-3 is LiODFP. The electrolyte formula used in experimental group 3-4 is different from the electrolyte formula used in experimental group 1-1 of Example 1 in that the electrolyte formula of experimental group 3-4 does not contain a lithium salt additive, that is, the lithium-containing raw material in the electrolyte formula of experimental group 3-4 is only LiPF6. Taking the electrolyte formula used in experimental group 1-1 of Example 1 as a reference, the LiPO2F2 contained in the electrolyte formula is discarded, and the original content of LiPO2F2 in the electrolyte formula is supplemented by the organic solvent component used in the electrolyte formula in an equal amount, and the electrolyte formula obtained in this way is used as the electrolyte formula used in experimental group 3-4.

[0087] Experimental group 3-1, experimental group 3-2, experimental group 3-3, and experimental group 3-4 were prepared according to the electrolyte formula composition they adopted. First, the materials used to prepare the organic solvent component were mixed evenly to obtain the organic solvent component. Then, at 10°C and in an argon atmosphere, the formulated amounts of VC, PS, lithium salt additives, silicon oxide I, and LiPF6 were added to the organic solvent component. The temperature was maintained at 10°C, and the resulting mixture was fully stirred until the solid material was fully dissolved to obtain a uniform solution, thereby making an electrolyte.

[0088] Preparation Example 3

[0089] The electrolyte used to prepare the lithium ion battery in this preparation example is the electrolyte prepared in Example 3. The electrolyte prepared in Example 3 was used to prepare the lithium ion battery in the same manner as in Preparation Example 1. Except for the difference in the composition of the electrolyte used, the other materials and related process steps used in preparing the lithium ion battery in this preparation example were consistent with those in Preparation Example 1.

[0090] Test Example 3

[0091] 1. Test subjects

[0092] The soft-pack battery prepared in Preparation Example 3 was used as a test object.

[0093] 2. Test items

[0094] The Xinwei charge and discharge test cabinet is used to conduct cycle performance test on the test object.

[0095] (1) Normal temperature cycle performance test

[0096] The relevant operations are consistent with those in Test Example 1.

[0097] (2) High temperature cycle performance test

[0098] The relevant operations are consistent with those in Test Example 1.

[0099] 3. Test results

[0100] The test results are shown in Table 5. For ease of comparison, Table 5 shows the high-temperature cycle performance test results of the lithium-ion battery based on the electrolyte provided by Experimental Group 1-1 in Example 1 measured in Test Example 1. Therefore, the electrolyte formula of Experimental Group 3-4 does not contain lithium salt additives. Therefore, the content of lithium salt additives in Table 5 corresponds to the position of Experimental Group 3-4 represented by “-”.

[0101] Under the same test conditions, compared with the lithium-ion batteries using the electrolyte of experimental group 3-4 without lithium salt additives, the lithium-ion batteries using the electrolyte of experimental group 1-1, the electrolyte of experimental group 3-1, the electrolyte of experimental group 3-2, and the electrolyte of experimental group 3-3 can achieve higher capacity retention rates. Further, by comparing the test data of lithium-ion batteries using the electrolyte of experimental group 1-1, the electrolyte of experimental group 3-1, the electrolyte of experimental group 3-2, and the electrolyte of experimental group 3-3, it can be seen that the capacity retention rate of the lithium-ion batteries using the electrolyte of experimental group 1-1 using LiPO2F2 as a lithium salt additive under the same conditions is significantly higher than that of the lithium-ion batteries using other electrolytes in this test example. In the electrolyte formula of experimental group 1-1, based on the application of functional additive A, LiPO2F2 is further selected as a lithium salt additive. In the electrolyte thus prepared, functional additive A and LiPO2F2 are used together as film-forming materials on the surfaces of the positive and negative electrodes. When the above-mentioned electrolyte is used under high-voltage working conditions, the functional additive A and LiPO2F2 in the electrolyte synergize to effectively enhance the film-forming effect of the positive and negative electrodes, so that the lithium-ion battery using the electrolyte provided by experimental group 1-1 of Example 1 can achieve significantly better cycle stability than other lithium-ion batteries.

[0102] Table 5. Test result statistics of test case 3

[0103]

[0104] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A pressure-resistant electrolyte, characterized in that: The electrolyte comprises an organic solvent component, a lithium salt component and an additive component, wherein the additive component comprises a functional additive A; The general structural formula of the functional additive A is: wherein R11, R12, and R13 are independently selected from hydrogen or C1-C4 alkyl or C1-C4 substituted alkyl, R2 is cyanomethyl or cyanoethyl, and at least one of R3 and R4 includes a carbon-carbon double bond; The molar mass of the functional additive A is 180-280, and in the voltage-resistant electrolyte, the mass proportion of the functional additive A is 0.3wt.%-1wt.%.

2. The pressure-resistant electrolyte according to claim 1, characterized in that: The general structural formula of the functional additive A is: Among them, R5 is hydrogen or C1-10 alkyl or C1-10 alkoxy or C1-10 halogenated alkyl or C1-10 halogenated alkoxy, and R6 is alkyl or substituted alkyl.

3. The pressure-resistant electrolyte according to claim 2, characterized in that: The general structural formula of the functional additive A is: R7, R8, R9, and R10 are independently selected from hydrogen or C1-10 alkyl or C1-10 alkoxy or C1-10 halogenated alkyl or C1-10 halogenated alkoxy.

4. The pressure-resistant electrolyte according to claim 1, characterized in that: The additive component further includes a sulfur-containing additive and vinylene carbonate, wherein the sulfur-containing additive includes at least one of vinyl sulfate, 1,3-propane sultone, and 1,3-propylene sultone, and the carbonate additive includes vinylene carbonate; The lithium salt component includes lithium hexafluorophosphate and a lithium salt additive, and the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium bis(oxalatoborate), and lithium difluorobis(oxalatophosphate).

5. The pressure-resistant electrolyte according to claim 4, characterized in that: The sulfur-containing additive includes 1,3-propane sultone.

6. The pressure-resistant electrolyte according to claim 4, characterized in that: The lithium salt additive includes lithium difluorophosphate.

7. The pressure-resistant electrolyte according to claim 4, characterized in that: Calculated by mass ratio, the functional additive A: the sulfur-containing additive: the lithium salt additive = 0.3-1: 0.5-3: 0.5-1.

8. The pressure-resistant electrolyte according to claim 4, characterized in that: The organic solvent component includes cyclic carbonates, chain carbonates and chain carboxylates.

9. The pressure-resistant electrolyte according to claim 8, characterized in that: The cyclic carbonate includes fluoroethylene carbonate and ethylene carbonate, the chain carbonate includes diethyl carbonate, the chain carboxylic acid ester includes diethyl carbonate, and the chain carboxylic acid ester includes ethyl difluoroacetate; in the voltage-resistant electrolyte, the total mass of fluoroethylene carbonate and ethylene carbonate: the mass of diethyl carbonate: the mass of ethyl difluoroacetate = 1 to 15: 2 to 70: 5 to 20.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the pressure-resistant electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silyl ester phosphinates as electrolyte additives

    CN109792084A

  • Lithium ion battery electrolyte and lithium ion battery thereof

    CN115548442A

  • Lithium ion electrolyte and lithium ion battery

    CN118352640A

  • Lithium ion battery electrolyte and lithium ion battery

    CN119108642A

  • Additive agent for nonaqueous electrolyte, nonaqueous electrolyte using the same, and nonaqueous electrolytic secondary battery

    JP2018037388A